PENGARUH PERAN PENDAMPING UMKM TERHADAP PENINGKATAN PERFORMA UMKM DI KOTA BANDUNG - Uyuandi, Agus Elga; Sudiapermana, Elih; Kamarubiani, Nike (Comm-Edu (Community Education Journal), 2024)
Micro, Small and Medium Enterprises (SMEs) play an important role in the development of the national economy. However, the importance of this sector has not been offset by its contribution to the value of Gross Domestic Product (GDP), which is still relatively low when compared with the population of SMEs perpetrators of 99.9%. Therefore, this study aims to analyze the influence of the role of SMEs accompaniment on the improvement of SMEs performance with the mediation of the variable SMEs managerial ability. The data was collected using an angket of 360 respondents taken using a simple random sampling approach on SMEs perpetrators in the district of Bandung which is included in the SMEs Associate Programme of Cooperative Services and the SMEs of Bandung. The result was a significant direct influence of the accompaniment role on managerial capabilities, a significant influence on the accompanying role on the performance of SMEs, and a mediation influence in which the management ability served as the mediation variable, in other words, mediating the indirect influence that the accomplishment role had on SMEs performance. This study provided useful insights for policymakers in developing SMES support programmes